2021
DOI: 10.1002/ijgo.13561
|View full text |Cite
|
Sign up to set email alerts
|

Physical methods for the treatment of genitourinary syndrome of menopause: A systematic review

Abstract: Background Genitourinary syndrome of menopause (GSM) negatively affects sexual function and quality of life. Techniques like laser and radiofrequency are being used to manage GSM, particularly in women with contraindications for hormone therapy. Objectives To verify whether the physical methods of laser and radiofrequency can be recommended as safe and effective options for the treatment of GSM/urinary urgency or incontinence in pre‐ and postmenopausal women. Search strategy Databases were comprehensively sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 56 publications
(279 reference statements)
0
22
0
Order By: Relevance
“…The CO 2 laser has been demonstrated to be an efficacious therapy for managing all GSM symptoms up to 12 months after treatment. 32 The VHI score improved concerning elasticity, fluid volume, pH, epithelial integrity and vaginal moisture, and VAS scores improved considerably for sensitivity, vaginal dryness, itching/stinging, dyspareunia and dysuria. The studies about the Er:YAG treatment showed that this method is effective, practical and safe too, and the effects are rapid and sustained for at least 12 months.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The CO 2 laser has been demonstrated to be an efficacious therapy for managing all GSM symptoms up to 12 months after treatment. 32 The VHI score improved concerning elasticity, fluid volume, pH, epithelial integrity and vaginal moisture, and VAS scores improved considerably for sensitivity, vaginal dryness, itching/stinging, dyspareunia and dysuria. The studies about the Er:YAG treatment showed that this method is effective, practical and safe too, and the effects are rapid and sustained for at least 12 months.…”
Section: Discussionmentioning
confidence: 91%
“…21 28 Some systematic reviews have already been published on the subject. [29][30][31][32] A recent study assessing the physical methods for the treatment of GSM showed that, among physical methods, the CO 2 laser continues to be one of the most commonly used methods, as it has the largest body of scientific evidence. The CO 2 laser has been demonstrated to be an efficacious therapy for managing all GSM symptoms up to 12 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were not included in the literature review because they do not include women with UF, but they further highlight the need for patient counselling prior to hysterectomy [65]. Finally, the risk of stress UI may increase with hormone deprivation and postmenopausal status [66,67]. The impact of hysterectomy on hormonal status is discussed in the next section.…”
Section: Impact Of Hysterectomy On Pelvic Anatomy and Lower Urinary Tract Symptomsmentioning
confidence: 99%